Drawn to the special attention of the House : Draft Postal Packets (Miscellaneous Amendments) Regulations 2023 ; Russia (Sanctions) (EU Exit) (Amendment) (No. 3) Regulations 2023 ; Correspondence: Draft Pensions Dashboards (Amendment) Regulations 2023 : 46th Report of Session 2022–23 /: Draft Postal Packets (Miscellaneous Amendments) Regulations 2023 ; Russia (Sanctions) (EU Exit) (Amendment) (No. 3) Regulations 2023 ; Correspondence: Draft Pensions Dashboards (Amendment) Regulations 2023 : 46th Report of Session 2022–23. ([2023-07-13]) - Unknown
No abstract available